Electrochemical taste sensor for unmasking extra-virgin olive oils adulterated with rancid or winey-vinegary olive oils - Veloso, Ana C.A. (2020)
Olive oils may be commercially classified, in a decrease order of quality and economic value, as extra-virgin (EVOO), virgin (VOO) or lampante (LOO) olive oils, being quite prone to frauds. Thus legal protection regulations have been approved by the European Union Commission [1,2], being required the fulfilment of several physicochemical and sensory thresholds [3,4]. Unfortunately, the mixture of expensive olive oils with low quality oils aiming fraudulent economic revenue is still a common practice difficult to detect. In this work, a potentiometric electronic tongue (E-tongue) was used to detect adulteration of an EVOO with different added levels (2.5%, 5%, 10%, 20% and 40%; v/v) of an LOO with an intense sensory defect (rancid or wineyvinegary). Previously, similar electrochemical devices, also comprising lipid polymeric sensor membranes, showed to be able to give qualitative and/or quantitative responses towards basic taste sensations (acid, bitter, salty, sweet, and umami), positive sensory attributes (bitter, fruity, green and pungency) or defects (e.g., butyric, musty, putrid, winey-vinegary and zapateria) [5-8]. The E-tongue coupled with linear discriminant technique (based on the signal profiles of 19 or 20 E-tongue sensors, chosen using a simulated annealing meta-heuristic variable selection algorithm, for rancid and wineyvinegary adulterations, respectively) allowed to semi-quantitatively distinguish olive oils with different adulteration levels (repeated K-fold crossvalidation predictive correct classifications of 84±10% and 94±8% for rancid and winey-vinegary adulterations, respectively). The preliminary results showed the practical potential of the E-tongue as a taste device for the successful detection of EVOOs adulterated with LOO containing organoleptic defects.